2020
DOI: 10.1111/tpj.14685
|View full text |Cite
|
Sign up to set email alerts
|

Rapid systemic signaling during abiotic and biotic stresses: is the ROS wave master of all trades?

Abstract: Rapidly communicating the perception of an abiotic stress event, wounding or pathogen infection, from its initial site of occurrence to the entire plant, i.e. rapid systemic signaling, is essential for successful plant acclimation and defense. Recent studies highlighted an important role for several rapid whole-plant systemic signals in mediating plant acclimation and defense during different abiotic and biotic stresses. These include calcium, reactive oxygen species (ROS), hydraulic and electric waves. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
185
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(205 citation statements)
references
References 67 publications
(160 reference statements)
0
185
0
Order By: Relevance
“…Oxidation of membrane lipids by reactive oxygen species and radicals was originally considered a purely deleterious process-but it is now clear that enzymatic lipid peroxidation gives rise to a host of derivatives that act as hormonal gene regulators [64], including the above-mentioned inflammation-terminating hormones [65]. Moreover, ROS provide input into a host of signal transduction networks, that control not only defense against invaders, but also multiple aspects of growth, development, and reproduction of living organisms, including humans [66,67] and plants [68]. While excess ROS can be damaging, moderate ROS levels are thus a vital source of information and defense in all life forms.…”
Section: Enhancement Of Eye and Brain Function Beyond Diseasementioning
confidence: 99%
“…Oxidation of membrane lipids by reactive oxygen species and radicals was originally considered a purely deleterious process-but it is now clear that enzymatic lipid peroxidation gives rise to a host of derivatives that act as hormonal gene regulators [64], including the above-mentioned inflammation-terminating hormones [65]. Moreover, ROS provide input into a host of signal transduction networks, that control not only defense against invaders, but also multiple aspects of growth, development, and reproduction of living organisms, including humans [66,67] and plants [68]. While excess ROS can be damaging, moderate ROS levels are thus a vital source of information and defense in all life forms.…”
Section: Enhancement Of Eye and Brain Function Beyond Diseasementioning
confidence: 99%
“…A systemic response that induces acclimation mechanisms in remote tissues is termed systemic acquired acclimation (SAA; Karpinski et al, 1999), and this process was found to be essential for plant survival under different abiotic stress conditions (Suzuki et al, 2013;Devireddy et al, 2018;Zandalinas et al, 2019Zandalinas et al, , 2020. SAA is controlled by the integration of rapidly propagating systemic signals such as the reactive oxygen species (ROS), calcium, and hydraulic waves, as well as electric signals (Suzuki et al, 2013;Fichman and Mittler, 2020b). The ROS wave is a cell-tocell process of ROS-induced ROS production that propagates from the particular tissue that initially senses the stress to the entire plant (Fichman et al, 2019).…”
mentioning
confidence: 99%
“…The ROS wave is a cell-tocell process of ROS-induced ROS production that propagates from the particular tissue that initially senses the stress to the entire plant (Fichman et al, 2019). It is activated in response to various stimuli, such as pathogen infection, wounding, heat, and high light (HL) stresses and is dependent on the function of the respiratory burst oxidase homolog D (RBOHD) protein (Fichman and Mittler, 2020b).…”
mentioning
confidence: 99%
“…The systemic stomatal response of soybean appeared to occur at a rate comparable to that of Arabidopsis (6 min to transverse ;25-cm distance; Fig. 1), suggesting that it too could be mediated by systemic ROS signals (Fichman and Mittler, 2020). To test this hypothesis, we applied the ROS/redox inhibitor diphenyleneiodonium (DPI; 50 mM), or water, in agarose solution (0.3%) to the stem-petiole junction of the lower leaf for 40 min before applying the 40 to 1,500 mmol m 22 s 21 light-change treatment to the upper (local) leaf ( Fig.…”
mentioning
confidence: 92%